The danse macabre: the fiction of J.P. Donleavy and Henry Miller - Harris, Peter James (ABEI Journal, 2006)
The work of two writers, J.P. Donleavy and Henry Miller is compared. It is argued that the anarchic behaviour of the characters in the fiction of both writers is in defiance of the void they perceive to be at the centre of things, an exuberance in the face of death, a danse macabre.